Edukasi Kesehatan Reproduksi sebagai Pencegahan Kehamilan pada Remaja di Madrasah Aliyah Negeri Seram Bagian Barat - Siti Rochmaedah; Trysna Ayu Sukardi; Syahfitrah Umamity (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Adolescence is an important period for reproductive health because it is a period of behavioral formation, where at this time, teenagers begin to try new or challenging things, including in health behavior, one of which is free sex behavior. This free lifestyle behavior is greatly influenced by a correct understanding of adolescent reproductive health. The impact that can occur due to free sex behavior is early pregnancy or Unwanted Pregnancy. Adolescent pregnancy is one of the health problems that requires serious attention so that efforts are needed to increase awareness of reproductive health for all teenagers. The purpose of this community service is to increase the knowledge of teenagers at MAN Seram Bagian Barat about reproductive health and increase adolescent awareness in preventing early pregnancy. The method used is to provide education to teenagers at Madrasah Aliyah Negeri Seram Bagian Barat. Teenagers are very enthusiastic about this activity by asking various questions and the active discussion makes teenagers more enthusiastic. The final result is that 26 teenagers have good knowledge after being given education, from previously only 11 teenagers. The conclusion is that teenagers understand how to prevent early pregnancy in teenagers at MAN Seram Bagian Barat. It is hoped that good knowledge will prevent teenagers from engaging in free sex behavior that can result in pregnancy at a young age.